Cost of physiotherapy non-attendance at a metropolitan hospital in Australia: A time-driven activity-based costing study - Hannah E Carter; Sanjeewa Kularatna; Steven M McPhail; Sundresan Naicker; Shayma Mohammed Selim; Samantha Borg; Codie Armstrong; Melanie Walkenhorst; Brittney Kunst (BMJ Open)
Objectives (1) Identify the processes, staff time and labour costs associated with non-attendance at two physiotherapy outpatient clinics using time-driven activity-based costing; (2) estimate labour cost-burden of non-attendance response scenarios.Design A six-step time-driven activity-based costing method was used, including scenario analyses.Setting Two tertiary hospital outpatient clinics.Participants Clinic non-attendance rates were determined from digital administrative records for participating clinics. Interviews and iterative discussions were conducted with 15 administrative and clinical staff to establish process maps and key parameters.Primary and secondary outcome measures The primary outcome was health service labour cost associated with clinic non-attendance. Four key work processes were identified and costed (2023, A$).Results Clinic non-attendance rates for the 2018–2021 period were 8% (Clinic 1) and 10% (Clinic 2). Complex triaging cases constituted greater costs than simple triaging cases. Projected annual costs of non-attendance were as high as A$114 827 for a single clinic. The most expensive referral and response scenario was internal referral with non-attendance that was converted to a telephone appointment (mean cost of A$113/appointment).Conclusion Non-attendance rates at participating clinics were at the lower end of values reported in prior literature; however, substantial healthcare resource waste was still evident. Findings highlighted the extent to which non-attendance at scheduled clinic appointments may not only impact patients’ welfare through lost treatment opportunity, but also carry substantial opportunity cost from wasted hospital resources that could have been allocated to other referred patients. Establishing the effectiveness and cost-effectiveness of interventions to reduce non-attendance remains a priority.